Kajian Edible Coating Berbasis Kolang-Kaling dengan Penambahan Bahan Pengental dari Sumber Alami (Pati dan Pektin) dan Sintetis (CMC) yang Diaplikasikan pada Dodol - Pramsiska, Dwi; Harini, Noor; Winarsih, Sri; Manshur, Hanif Alamudin (Food Technology and Halal Science Journal, 2020)
The purpose of this study was to determine the effect of the type of thickener on the quality of edible coatings, the effect of the concentration of thickener types on the quality of edible coatings applied to dodol, and find the best treatment of edible coatings that can increase the shelf life of dodol. The research was arranged in a Nested Randomized Design method consisting of two factors. First factor that became the nest was a variation of thickener (P) with treatment level (Pati, Pectin, and CMC) and second factor that became nested namely variation of thickener concentration (K) with treatment level (1%, 1.5%, and 2% ). The results showed that the addition of pectin 2% as the best treatment has a viscosity of 238.2 cP and the ability to protect dodol on the 6th-day storage can be observed at a water content of 26.98% which is close to SNI which is equal to 20%, TPC (Total Plate Count) 4.9 × 104Cfu / g which is close to the TPC number on SNI of 1 × 104Cfu / g, FFA (Free Fatty Acid) of 1.06% which does not exceed the SNI limit of 10.5%, the texture of 8.18 N / mm, the aroma score of 3.53 is a bit rancid, the appearance score is 5.23 which means neutral and the preferences score is 6.07 which means a little like.